Stunting Prevention with the Active Role of Families in Manis Jaya Village, Tangerang City - Ellyssa Kusuma Laksanawati; Rofiroh Rofiroh; Riki Candra Putra; Ahmad Iskandar; Bambang Suhardi Waluyo (Journal of Community Service in Science and Engineering (JoCSE), 2023)
Stunting or growth disorders in children is a global health problem that has a significant impact on children's physical and cognitive development. Stunting prevention is a top priority in efforts to improve the quality of life and the younger generation's future. This community service aims to provide an understanding of the importance of preventing stunting, the risk factors involved, and strategies that can be implemented to reduce stunting rates among residents in Manis Jaya Village, Tangerang City. The method used to achieve the goals and targets of stunting prevention is through outreach/lectures, including education on the role of families in improving nutrition, promotion of exclusive breastfeeding and nutritious food, and increasing access to essential health services. It is hoped that the results of the activity will prevent stunting from being the responsibility of the government, health organizations, and the entire community. Collaboration between the government, private sector, NGOs, and village communities will be vital in achieving stunting prevention targets. Stunting atau gangguan pertumbuhan pada anak-anak merupakan masalah kesehatan global yang berdampak besar pada perkembangan fisik dan kognitif anak-anak. Pencegaha stunting menjadi prioritas utama dalam upaya meningkatkan kualitas hidup dan masa depan generasi muda. Pengabdian masyarakat ini bertujian memberikan pemahaman mengenai pentingnya pencegahan stunting, faktor-faktor risiko yang terlibat serta strategi yang dapat diimplementasikan untuk mengurangi angka stunting pada warga di Kelurahan Manis Jaya Kota Tangerang.  Metode yang digunakan untuk mencapai tujuan dan target pencegahan stunting adalah dengan penyukuhan/ceramah mecakup edukasi peran keluarga dalam peningkatan gizi, promosi pemberian asi eksklusif dan makanan bergizi serta peningkatan akses ke layanan kesehatan dasar. Hasil dari kegiatan diharapkan pencegehana stunting bukan hanya tanggung jawab pemerinta dan organisasi kesehatan tetapi  juga seluruh masyarakat. Kolaborasi antara pemerinta, sector swasta, LSM dan masyarakat desa akan memainkan peran kunci dalam mencapai target pencegahan stunting.